Design options and sources of bias in time-to-pregnancy studies - Olsen, Jørn (Scandinavian Journal of Work, Environment & Health, 1999)
Studies of fecundity are few, and there is a need to know how fecundity develops over time and to identify its determinants. Since fecundity is best measured by studying time to pregnancy, valid and well-recognized instruments are needed for data collection. A standardized questionnaire on fecundity not only has to obtain information on waiting time, but also information on the importance of evaluation results. The use of contraceptive methods, the understanding of family planning, and behavioral changes driven by past reproductive experience are issues of importance for designing and interpreting results, as are other sources of bias also.
Keywords: epidemiology; fecundity